Implementasi Kebijakan Program Dinas Sosial Terhadap Penyandang Masalah Kesejahteraan Sosial Pada Gelandangan dan Pengemis di Kabupaten Karimun - Hafzana Bedasari; Endang Tri Wahyuni (UIR Press, 2020)
This research is backgrounded by one of the people with social welfare problems in homeless and beggars whose one factor is poverty, social services karimun district through social service regulations make policy a program in dealing with social welfare problems. This study aims to find out more about the implementation of government program policies in addressing social welfare problems in homeless and beggars and to know the factors that influence the implementation of government program policies in dealing with social welfare problems in homeless and beggars in karimun district. Data collection techniques used are unstructured interviews and Field Observation and Documentation. Data sources are obtained by using secondary and primary data. Data analysis used in this research is qualitative data analysis method. From the results of this study obtained an idea that the overall Implementation of Social Service Program Policy on People with social welfare problems in Homeless and Beggars in Karimun Regency, namely: Transmission, Clarity, Consistency, Human Resources, Budget resources, Equipment Resources, Authority Resources, Bureaucratic Appointments, Incentives, Standard operational procedure (SOP), Fragmentation, then from the indicators can be known that the implementation of social service program policy towards people with social welfare problems in homeless and beggars in Karimun Regency has been running well in accordance with the results of research from interviews with 5 key informants as a source of data selected deliberately (purposive sampling) namely, Head of social rehabilitation, Head of social rehabilitation section of people with disabilities and social tuna, Social problems rehabilitation analyst, Satpol PP, Bum and beggars. Supporting factors that influence the implementation of the program policy karimun Social Service Communication, Resources, Disposition, Bureaucratic Structure.